PEMBUATAN WEB SERVICE DENGAN GOOGLE SPREADSHEETS SEBAGAI SOLUSI INTEGRASI APLIKASI MULTIPLATFORM - Lailyn Puad; Rike Limia Budiarti; Nabila Zahra (Jurnal Informatika Kaputama (JIK), 2021)
Multiplatform application development is an unavoidable technological demand. Startup industries are increasingly emerging by offering convenience from various aspects of life, retail, finance, green life, artificial intelligence to the Internet of Things. This is in line with the increasing growth of innovation both systemically and technically, it does not rule out the possibility that these innovations include ways to use the minimum resources possible to produce the maximum possible output. The use of the Restfull API is a good solution to solve this problem, the output, which can be a JSON file, can be communicated with various application platforms. This study will review the use of popular applications such as Google Spreadsheets to become a media provider for web services. This method is implemented in the process of updating student data at the Nurdin Hamzah University in the Dikti Feeder.